Fungal contamination of medicinal cannabis: A bibliometric evaluation, trends, and future perspectives - Alzate, Paola; Shiroma, Maria Clara [UNESP]; Castro-Ríos, Katherin (Universidad Nacional de Trujillo, 2024)
Fungal contamination is an important problem in cannabis and medical cannabis production, as fungi can produce toxic compounds or reduce the quality and safety of the product. The aim of this study was to perform a bibliometric evaluation related to fungal contamination in cannabis, analyzing current trends in this field and providing future perspectives for research. For this purpose, an exhaustive search was carried out in the scientific literature in electronic databases such as Scopus and Web of Science (WOS), covering the period from 2000 to 2023. The results obtained were processed through bibliometrics and network analysis, using tools such as RStudio and Bibliometrix software. The results revealed that the main themes associated with fungal contamination in cannabis are focused on: diseases related to fungal contamination of the plant, use of fungi as an alternative biological control in cannabis cultivation, metabolites associated with cannabis and their potential in fungal control, as well as fungal diversity in cannabis cultivation and postharvest and the risk to consumer health. Finally, future research areas are proposed to address the challenge of fungal contamination in medicinal cannabis production, covering topics such as pest control, contamination, genetic resistance, active compounds, analysis methods, and the impact of fungi on cannabis.
Contaminação fúngica da cannabis medicinal: Avaliação bibliométrica, tendências e perspectivas futuras
Keywords: bibliometric analysis; biological control; cannabis production; fungi in cannabis; risks of contamination; Tree of Science